OPTIMASI RUTE PENGIRIMAN BUAH KELAPA DI PASAR TRADISIONAL KABUPATEN MOJOKERTO MENGGUNAKAN ALGORITMA GENETIKA - Yusril Adil Hidayat; Maulana Ardillan Arendra; Yesy Diah Rosita (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Traditional markets are markets set up by the state or the private sector to carry out business in the form of stalls, shops, or kiosks. One that is often found in traditional markets is coconut. Coconut is a type of plant that is found in almost all tropical countries, including Indonesia. a very popular commodity for the food needs of the Indonesian people, especially food made from coconut milk and grated coconut. Delivery of coconuts from producers to suppliers can take a long time; for this reason, market traders who sell coconuts do not bring them from the farmers themselves; stock coconuts are obtained from suppliers. This study aims to solve the problem of the optimal route for shipping coconuts in order to obtain the effectiveness of the minimum distance. In this case, the application of the TSP (Traveling Salesman Problem) is a solution to the logistics planning problem using a method, namely the Genetic Algorithm. This test uses two clusters: 10-8-2-3-9-5-6-1-4-7 and 5-1-3-4-2, with optimal results of 36.5935 km. This research covers the area in Mojokerto district.